2011
DOI: 10.1016/j.ajpath.2010.11.071
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Activin Type IIB Receptor to Improve Muscle Mass and Function in the mdx Mouse Model of Duchenne Muscular Dystrophy

Abstract: The activin receptor type IIB (ActRIIB) is a transmembrane receptor for transforming growth factor-␤ superfamily members, including myostatin, that are involved in the negative regulation of skeletal muscle mass. We tested the translational hypothesis that blocking ligand binding to ActRIIB for 12 weeks would stimulate skeletal muscle growth and improve muscle function in the mdx mouse. ActRIIB was targeted using a novel inhibitor comprised of the extracellular portion of the ActRIIB fused to the Fc portion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
90
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(106 citation statements)
references
References 57 publications
13
90
3
Order By: Relevance
“…Blockade of AcvR2B ligands can be achieved, e.g. by using the soluble ligand binding domain of type IIb activin receptor fused to the Fc domain (sAcvR2B-Fc) to effectively increase muscle size [18][19][20][21]. Blocking these proteins using various strategies has been shown to attenuate dystrophic pathology of the mdx mouse in some [18,22], but not in all studies [20,23].…”
Section: Introductionmentioning
confidence: 99%
“…Blockade of AcvR2B ligands can be achieved, e.g. by using the soluble ligand binding domain of type IIb activin receptor fused to the Fc domain (sAcvR2B-Fc) to effectively increase muscle size [18][19][20][21]. Blocking these proteins using various strategies has been shown to attenuate dystrophic pathology of the mdx mouse in some [18,22], but not in all studies [20,23].…”
Section: Introductionmentioning
confidence: 99%
“…It is also reported that the potent cell surface receptor ActRIIB binds and inhibits myostatin, leading to dramatic muscle growth (24)(25)(26). Based on this background, we hypothesized that the combination of these two agents would have a therapeutic advantage.…”
Section: Discussionmentioning
confidence: 99%
“…Ligands, including myostatin and growth differentiation factor-11 (GDF-11), bind to the ActRIIB, leading to phosphorylation and nuclear translocation of Smad2/3, which mediates muscle atrophy (20). Interestingly, the soluble ligandbinding domain of ActRIIB fused to the Fc domain of IgG (ActRIIB-Fc) potently binds and inhibits TGF-␤ family members in muscle, leading to rapid and dramatic muscle growth both in vitro and in vivo (21)(22)(23)(24).…”
mentioning
confidence: 99%
“…Another study explored the possibility of inhibiting myostatin by using RNAi against ActRIIb and restore quasi dystrophin by AAV-U7 mediated exon skipping in a mouse model of muscular dystrophy (Dumonceaux et al, 2010). Recently in the same animal model the use of soluble ligands of ActRIIb as peptides, including the extracellular portion of the ActRIIb fused to the Fc portion of murine IgG (sActRIIb), has been shown to improve skeletal muscle mass and functional strength (Pistilli et al, 2011).…”
Section: Inactivation Of Activin Receptor Iibmentioning
confidence: 99%